2012
DOI: 10.1162/jocn_a_00177
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gates to Consciousness: Distractors Activate a Central Inhibition Process

Abstract: The paradigm of distractor-induced blindness has previously been used to track the transition from unconscious to conscious visual processing. In a variation of this paradigm used in this study, participants (n = 13) had to detect an orientation change of tilted bars (target) embedded in a dynamic random pattern; the onset of the target was signaled by the presentation of a color cue. Occasional orientation changes preceding the cue served as distractors and severely impaired the target's detection. ERPs showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
43
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 67 publications
12
43
1
Order By: Relevance
“…Niedeggen, Hesselmann, Sahraie, Milders, and Blakemore (2004) recorded ERPs during a distractor-induced blindness paradigm and concluded that the inhibition of target perception occurs at a post-sensory level. In a later study, moreover, they showed that the inhibition causes an ERP EEG negativity over frontal cortical areas (Niedeggen et al, 2012). These results fit well with our proposal that access to consciousness is controlled by those BG pathways that modulate activity in the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Niedeggen, Hesselmann, Sahraie, Milders, and Blakemore (2004) recorded ERPs during a distractor-induced blindness paradigm and concluded that the inhibition of target perception occurs at a post-sensory level. In a later study, moreover, they showed that the inhibition causes an ERP EEG negativity over frontal cortical areas (Niedeggen et al, 2012). These results fit well with our proposal that access to consciousness is controlled by those BG pathways that modulate activity in the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 84%
“…In conclusion, Dehaene et al (2003) proposed a sensory model of access consciousness while we suggest a cognitive model of access consciousness. In line with our cognitive focus, Niedeggen et al (2012) observed a distractor-related EEG negativity over frontal cortical areas in their distractor-induced blindness paradigm, but no modulation of EEG activity over posterior, sensory cortices.…”
Section: Comparison With Previous Modelssupporting
confidence: 81%
See 2 more Smart Citations
“…Most of this work involves an empirical comparison between groups, treatments, or experimental conditions. For instance, Rouw and Scholte [30] compared a group of control participants with a group of Playing a first-person shooter video game induces neuroplastic change [34] Closing the gates to consciousness: Distractors activate a central inhibition process [35] TMS of the FEF interferes with spatial conflict [36] Local field potential activity associated with temporal expectations in the macaque lateral intraparietal area [37] Spatio-temporal brain dynamics mediating post-error behavioral adjustments [38] Hippocampal involvement in processing of indistinct visual motion stimuli [39] grapheme-color synesthetes, people who experience a specific color whenever they see a particular letter or number (e.g., "T is bright red"). Diffusion tensor imaging confirmed the hypothesis that the added sensations in synesthesia are associated with more coherent white matter tracts in various brain areas in frontal, parietal, and temporal cortex.…”
Section: Cognitive Neurosciencementioning
confidence: 99%